Analysis of Potential Code Vulnerabilities involving Overlapping Instructions - Al Sardy, Loui; Tang, Tong; Spisländer, Marc; Saglietti, Francesca (Computer Safety, Reliability, and Security SAFECOMP 2017 Workshops, ASSURE, DECSoS, SASSUR, TELERISE, and TIPS, 2017)
This article proposes approaches supporting the analysis of code vulnerabilities based on overlapping machine instructions of variable length. For the purpose of focusing the search for potential malicious code it is suggested to apply first disassembling techniques allowing for a restriction of potentially exploitable memory space. Successively, testing based on heuristic optimization may be applied in order to evaluate dynamically the practicality of vulnerability exploitation. <br
UnivIS-Import:2018-09-06:Pub.2018.tech.IMMD.lsinfs_1.constr
Keywords: security; vulnerability; overlapping instruction; redirection; testing

Constraint-based Testing for Buffer Overflows - Al Sardy, Loui; Saglietti, Francesca; Tang, Tong; Sonnenberg, Heiko (Computer Safety, Reliability, and Security SAFECOMP 2018 Workshops ASSURE, DECSoS, SASSUR, STRIVE, and WAISE, 2018)
This article proposes two heuristic approaches targeted at the optimized generation of test cases capable of triggering buffer overflows resp. underflows. Both testing techniques are based on guiding conditions statically derived by Integer Constraint Analysis. First experimental evaluations confirmed the superiority of local optimization algorithms over global ones. <br
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.lsinfs_1.analys
Keywords: software vulnerability; buffer overflow; integer constraint analysis; testing technique; global optimization; local optimization